Expression of Amino-Terminal Portions or Full-Length Viral Replicase Genes in Transgenic Plants Confers Resistance to Potato Virus X Infection. - Braun, CJ (1992)
The first open reading frame (ORF 1) of potato virus X (PVX) encodes a putative replicase gene. Transgenic tobacco lines expressing ORF 1 are resistant to PVX infection when inoculated with either PVX or PVX RNA. Analyses of lines containing various portions of the ORF 1 gene demonstrated that resistance is conferred to plants by expressing approximately the first half of the ORF 1 gene. One line expressing the untranslated leader and first 674 codons of ORF 1 is highly resistant to PVX infection. Conversely, lines expressing either approximately the third or fourth quarter of the ORF 1 gene, which contain the conserved nucleotide triphosphate (NTP) binding motif and Gly-Asp-Asp (GDD) motif, respectively, are not protected from PVX infection. In the resistant full-length and amino-terminal lines, lower numbers of local lesions were observed, and the virus accumulation in the inoculated and upper leaves was reduced when compared with the nontransformed control. When the performance of the most resistant ORF 1 line was compared with the most resistant coat protein (CP) line in a resistance test, the best ORF 1 line was more resistant to PVX infection than the best transgenic line expressing the PVX CP gene. These findings define a promising new approach for controlling plant viral infection.